The Strategic Role Of Article 6 Of Law No 41 Of 2004 In The Management Of Term Waqf: A Progressive Review Of Islamic Economic Renewal - Pratama, Tommy; Syahmirwan; Ar Rosyit, Achmad Nasrul Waton (Indonesian Scientific Publication, 2023)
Waqf is a form of worship and is also one of the pillars of the Islamic economy which has the potential to improve community welfare and overcome the problem of poverty. One of the laws governing waqf in Indonesia is Law No. 41 of 2004. Futures Waqf is an innovation in modern Islamic economics, aligning Islamic economic principles with contemporary developments. This research provides an understanding of the evolution of Islamic economics and efforts to encourage the implementation of Islamic economic principles in ever-changing global dynamics. In this research the author uses a qualitative method with a normative juridical approach. This law is the basis that waqf can be forever and can also have a term. This is very different from what is regulated by Islamic waqf law which tends to be less directed towards economic empowerment of the people and is only used for religious activities such as building mosques, prayer rooms, schools and cemeteries. This evaluation provides an in-depth impact on how the effectiveness of this regulation can increase the economic benefits of Term Waqf, encourage sustainable economic growth, and support the achievement of sharia economic development goals in Indonesia.